Enhancing academic success through the involvement of students in quality assurance and promotion in higher education: A synopsis - Saidi, A. (South African Journal of Higher Education, 2020)
One of the hallmarks of the democratisation of higher education is the involvement of students in the entire higher education delivery value chain. Global literature demonstrates a positive causal relationship between the involvement of students in the higher education delivery value chain and academic success. The article contends that, since quality assurance and promotion are acknowledged as integral components of the higher education delivery value chain, the involvement of students in quality assurance and promotion processes at the institutional and national levels can contribute positively towards enhancing academic success for students. The post-apartheid policies on higher education envisioned a transformed, effective and efficient higher education system, characterised by, among others, expanding access and improving student success. Unfortunately, while access has been expanding substantially, academic success of students has not improved significantly. This state of affairs requires that all stakeholders should have their hands on deck to contribute, through their diverse work activities, towards improving academic success of students. It is within this context that the CHE organised a conference on the theme: “Enhancing Academic Success through the Involvement of Students in Quality Assurance and Promotion in Higher Education”. This article provides a synopsis of the contribution of the conference to the discourse on enhancing the academic success through the involvement of students in quality assurance and promotion.